The uses of right heart catheterization in cardio-pulmonary disease: State-of-the-art - Bhavesh Katbamna; Lingling Wu; Mario Rodriguez; Phillip King; Joel Schilling; Jamal Mahar; Ajith P. Nair; Hani Jneid; Elizabeth S. Klings; Gerald L. Weinhouse; Sula Mazimba; Marc A. Simon; et al. (American Heart Journal Plus)
The right heart catheterization (RHC) remains an important diagnostic tool for a spectrum of cardiovascular disease processes including pulmonary hypertension (PH), shock, valvular heart disease, and unexplained dyspnea. While it gained widespread utilization after its introduction, the role of the RHC has evolved to provide valuable information for the management of advanced therapies in heart failure (HF) and cardiogenic shock (CS) to name a few. In this review, we provide a comprehensive overview on the indications, utilization, complications, interpretation, and calculations associated with RHC.